PROBLEMATIKA PENENTUAN BAIK DAN BURUK - Fauzi Yati (Saqifah: Jurnal Hukum Ekonomi Syariah, 2023)
In general, 'good' has the meaning of value which refers to happiness, satisfaction, enjoyment, valuable and useful for human life. Whereas 'bad' means actions, actions, attitudes, and behaviors that are hated by everyone; rejected by common sense and conscience; and declared disabled by a clear and clear mind. There are several understandings in determining good and bad. Socialism standardizes customs, hedonism is based on delicacy, enjoyment and biological lust, intuitionism refers to inner instincts, utilitarianism is guided by whether an action is useful or not, while religiousism is a measure of God's will and evolutionism is based on development from mediocre to perfection. Regarding reason and revelation, it can be drawn a common thread that reason is knowledge or knowledge that is obtained after going through a thought process. Whereas revelation is something that God has revealed to humans through the intermediary of the Prophet as a source of Shari'a. The Mu'tazilites prioritized reason over revelation. While Asy'ariyah otherwise.